Are data available for tracking progress on nutrition policies, programs, and outcomes in Pakistan? - Neupane, Sumanta; Jangid, Manita; Scott, Samuel P.; Nguyen, Phuong Hong; Kim, Sunny S.; Murira, Zivai; Torlesse, Harriet; Menon, Purnima (International Food Policy Research Institute, 2021)
The World Health Organization (WHO) and other global nutrition and health agencies recommend nutrition actions throughout the life-course to address malnutrition in all its forms. In this report, we examined how Pakistan’s nutrition policies and programs addressed recommended nutrition actions, nutrition outcomes, and the determinants of these outcomes. We reviewed population-based surveys and administrative data systems to assess the availability of data on nutrition actions and on indicators of determinants and outcomes. Our review identified a total of 53 recommended evidence-based nutrition actions, of which 51 were applicable to Pakistan; of those, 47 were addressed in nutrition policies and programs. Nutrition actions not included in current policies and programs were: daily iron and folic acid (IFA) supplementation and deworming during preconception; and food supplementation for complementary feeding, and daily IFA supplementation during early childhood. The Pakistan Multi-Sectoral Nutrition Strategy (PMNS) (2018–2025) was found to recognize and address all the key determinants of nutrition; it also expressed an intent to address all the Sustainable Development Goal (SDG) nutrition targets for maternal, infant, and young child nutrition. Targets for noncommunicable diseases (NCDs) were not currently set in the national strategies. Our data review found that, out of 47 actions that policies and programs addressed, population-based surveys contained data on 26 actions and administrative data sources contained data on 22 actions. Neither surveys nor administrative sources contained data on any actions aimed at adolescence, on energy and protein dietary supplements, on various types of counseling, on birth preparedness during pregnancy, or on optimal timing (delayed) of umbilical cord clamping; they also did not contain data on indicators related to newborn care, IFA supplementation around delivery and in the postpartum period, or counseling after growth monitoring during early childhood. The data gaps in population-based surveys on nutrition actions during early childhood were compensated for by the data on these nutrition actions that was available from administrative sources. Neither of the population-based surveys contained data on nutrition actions during early childhood such as breastfeeding counseling, counseling on appropriate complementary feeding, growth monitoring, and identification and management of severe acute malnutrition (SAM), or management of moderate acute malnutrition (MAM); administrative data sources, however, contained data on these actions. Population-based surveys contained data on most of the indicators on immediate and underlying determinants of undernutrition, but administrative data sources lacked data on indicators of immediate determinants. Population-based surveys contained data on all outcome indicators. In conclusion, Pakistan’s landscape for nutrition is robust, but there is limited consideration of targets for NCDs. The gaps in data availability for tracking progress on nutrition are much greater than are the gaps in policies and programs for addressing the recommended actions. Future population-based surveys and future modifications of other data systems should aim to fill the identified data gaps for nutrition actions.